ANALISIS IMPLEMENTASI COMPUTING CURRICULA 2020 DALAM PENDIDIKAN ILMU KOMPUTER - Gavin Berylian Josepto; Thomas Zugildo Magnus; Marvin Donald Richardo Aronggear; Jadiaman Parhusip (Informatika: Jurnal Teknik Informatika dan Multimedia, 2024)
Computing Curricula 2020 (CC 2020), published by ACM and IEEE, provides the latest guidelines for developing computer science education curricula worldwide. This journal analyzes the implementation and impact of Computing Curricula 2020 on computer science education. Special emphasis is placed on curriculum structure, the teaching of technical and non-technical skills, and adaptation to the evolving needs of the technology industry. Using data contained in Computing Curricula 2020, this journal explores how the curriculum serves as a guide to produce competent graduates who are industry-ready and understand the social and ethical implications of technology.